The Dynamic Cost of the Draft - Morten I. Lau; Panu Poutvaara; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2002)
We propose a dynamic general equilibrium model with human capital accumulation to evaluate the economic consequences of compulsory services (such as military draft or social services). Our analysis identifies a so far ignored dynamic cost arising from distortions in time allocation over the life-cycle. We provide conservative estimates for the excess burden that arises when the government relies on forced labor rather than on income taxation to finance public expenditures. Our results suggest that eliminating the draft could produce considerable dynamic gains, both in terms of GDP and lifetime utility.
Keywords: C68; H20; H57; J22; 330; conscription; draft; time allocation; distortionary taxation; computable general equilibrium models.